2004
DOI: 10.1080/1355785042000285375
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing food choices, dietary intake, and nutrition-related attitudes among African Americans: Application of a culturally sensitive model

Abstract: The findings suggest that the PEN-3 model is an appropriate framework for assessing how community and culture impact dietary habits of African Americans. African Americans will need information on basic nutrition topics such as serving sizes and reading food labels. The findings also suggest that programs and materials should be specifically developed for churches, neighborhood grocery stores, and local restaurants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
327
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(351 citation statements)
references
References 0 publications
19
327
1
4
Order By: Relevance
“…There was, however, popular support for mandatory labelling in studies, although conflicting findings have been found for consumers' willingness to pay extra for nutrition information (81) . Positive attitudes were higher among individuals reporting greater use of labels (56,59,85,108,110) ; however, negative attitudes were also prevalent in the literature (41,48,111,112) . Many consumers believed that serving sizes and health claims were misleading and were sceptical of the compliance of labels to regulatory law (85,113) .…”
Section: Income/educationmentioning
confidence: 92%
“…There was, however, popular support for mandatory labelling in studies, although conflicting findings have been found for consumers' willingness to pay extra for nutrition information (81) . Positive attitudes were higher among individuals reporting greater use of labels (56,59,85,108,110) ; however, negative attitudes were also prevalent in the literature (41,48,111,112) . Many consumers believed that serving sizes and health claims were misleading and were sceptical of the compliance of labels to regulatory law (85,113) .…”
Section: Income/educationmentioning
confidence: 92%
“…Cultural differences in exercise behaviors, food choice, and food preparation may serve as partial contributors ( Airhihenbuwa et al, 1996;James, 2004). In addition, investigators are becoming increasingly aware of the differential presence of environmental factors (for example, food deserts, inadequately built environment, systems of oppression, allostatic load) and psychosocial barriers (for example, reduced self-efficacy, binge eating, limited problem-solving skills) that affect the development of overweight and obesity among residents in low-income and racial and ethnic minority neighborhoods ( Chang, Nitzke, Guilford, Adair, & Hazard, 2008;Jeffery, Baxter, McGuire, & Linde, 2006;Taylor et al, 2013).…”
mentioning
confidence: 99%
“…Recent surveys indicate that 42 % of young adults do not meet recommendations for moderate or vigorous physical activity (Centers for Disease Control and Prevention 2012), while only 53 % report "eat[ing] to obtain or maintain a healthy weight" (American Heart Association and American Stroke Association 2011). Changing these health behaviors is difficult: the numerous barriers to improving physical activity and dietary behaviors among young adults include time and financial constraints and psychosocial and cultural influences (Myers and Roth 1997;Escoto et al 2012;James 2004;Turk et al 2012;Krist et al 2010;Walsh et al 2009;Greaney et al 2009). …”
Section: Discussionmentioning
confidence: 99%